EVALUATION OF ORS POWDER IN DIARRHEA TREATMENT OF AFGHAN IMMIGRANT CHILDREN IN ISFAHAN, 2022; A DESCRIPTIVE CROSS-SECTIONAL STUDY - Razia Miri; Sughra Alizada; Zahra Alizada; Murtaza Jafar (Scholar Express Journals, 2022)
Diarrhea is one of the deadly diseases in children. Diarrhea mortality rates are very important in the world, so they require serious treatment measures. ORS (Oral Rehydration Salt) can be considered as one of the effective drugs in the treatment of diarrhea. The level of mothers' awareness about using ORS powder is also one of the predisposing factors for effective treatment of diarrhea.
Keywords: Pediatric; diarrhea; ORS powder